Frecuencia y factores asociados a las enfermedades crónicas no transmisibles en adultos mayores en el Perú, año 2005 - Pajuelo Ramírez, Jaime (2022)
Introduction: Chronic non-communicable diseases are a public health problem. Objective: To determine the prevalence of chronic non-communicable diseases (NCD) in the elderly population and its association with Methods: adedumolts agragephd ic≥6fa0cyetoars. rs. The prevalenCross-sece of catiortenriaall hstuypedy rtefronm sioan, sedicaonbedates ry melsoulirctues, obe(ENIN si 2ty, 00me5), tabowhliicch isynncldroudemed  and dyslipidemia was estimated. Likewise, the association to demographic variables was determined (sex, age group, altitude of residence and area) through the prevalence ratio (PR) obtained by generalized linear models. Results: The sample was 620 AM, where three out of four presents at least one chronic non-communicable diseases. A prevalence of hypertension (36.3%), metabolic syndrome (31.0%), obesity (8.4%), diabetes mellitus (6.0%), low HDL-C (47.3%), hypertriglyceridemia (35.8%), hypercholesterolemia (28.4%) and high LDL-C (7.4%). Men presented lower frequency of obesity, metabolic syndrome and dyslipidemia (RPa 0.37, 0.27 and 0.56, respectively) compared to women. Likewise, residents at more than 3000 masl had lower prevalence of hypertension, diabetes mellitus, metabolic syndrome and dyslipidemia (RPa 0.56, 0.09, 0.23 and 0.71, respectively) compared to those who reside at less than 1000 masl. Conclusion: There is a significant presence of chronic non-communicable diseases in elderly population, the most prevalent being hypertension, metabolic syndrome, low HDL-C and hypertriglyceridemia. The female sex and people who lived in cities below 1000 masl were the most affected.